2017
DOI: 10.1093/bioinformatics/btx729
|View full text |Cite
|
Sign up to set email alerts
|

Complex analyses of inverted repeats in mitochondrial genomes revealed their importance and variability

Abstract: MotivationThe NCBI database contains mitochondrial DNA (mtDNA) genomes from numerous species. We investigated the presence and locations of inverted repeat sequences (IRs) in these mtDNA sequences, which are known to be important for regulating nuclear genomes.ResultsIRs were identified in mtDNA in all species. IR lengths and frequencies correlate with evolutionary age and the greatest variability was detected in subgroups of plants and fungi and the lowest variability in mammals. IR presence is non-random and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 29 publications
2
24
0
1
Order By: Relevance
“…DNA cruciforms are formed by S-IRs and with their important roles in replication, transcription and DNA stability it is not surprising that S-IRs are also present in cpDNA genomes. Analyses of mtDNA genomes revealed that S-IR sequences are abundant and nonrandomly distributed in the mitochondrial genomes of all living organisms, with particular abundance in regulatory regions such as replication origin and D-loop region [ 12 ]. Here, we analyzed all available cpDNA genomes for the presence of S-IRs capable of forming cruciform structures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA cruciforms are formed by S-IRs and with their important roles in replication, transcription and DNA stability it is not surprising that S-IRs are also present in cpDNA genomes. Analyses of mtDNA genomes revealed that S-IR sequences are abundant and nonrandomly distributed in the mitochondrial genomes of all living organisms, with particular abundance in regulatory regions such as replication origin and D-loop region [ 12 ]. Here, we analyzed all available cpDNA genomes for the presence of S-IRs capable of forming cruciform structures.…”
Section: Resultsmentioning
confidence: 99%
“…Both chloroplasts and mitochondria retain their own genomes and transcription machinery. S-IRs in mitochondrial DNA (mtDNA) are located nonrandomly with high abundance in the replication origin, D-loop, and stem-loop sequences [ 12 ]. While mitochondria are present in all eukaryotes, chloroplasts are exclusive for algae and plants.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several studies have demonstrated the important role of non-B-DNA structures in the context of gene regulation in bacteria [30,60,61]. For example, cruciforms have been shown to be important for dynamic genome organization [62], and for replication of the circular molecules of genomes, plasmids, mitochondrial DNAs [63], and chloroplast DNAs [64]. Cruciforms are targets for many architectural and regulatory proteins [10] and their importance has been demonstrated for the regulation of transcription of some genes [65].…”
Section: Biochemical and Cellular Impacts Of Simple Repeat Sequences mentioning
confidence: 99%
“…First, Goios et al 2006 examined the human mitogenomes to identify the direct and inverted repeat sequences [40]. Second, the study of Čechová et al 2018, which identified variability in the number of mitochondrial inverted repeat sequences in plants and fungi compared with mammals [41]. Third, the database and software developed by Shamanskiy et al 2019 to identify degenerated direct and inverted repeat sequences in mitochondrial DNA [23].…”
Section: Introductionmentioning
confidence: 99%